(untitled) - Asai, Kazuhiko (Tokyo, 1980)
This book introduce about significance of Getmanium. Germanium and health. Germanium in the treatment of disease in general. Germanium in the treatmant of cancer...
Keywords: Germanium,Germanium; Sử dụng trị liệu,Therapeutic use